Effective early reading - Bricknell's, Shirley (FEP International Australia, 2004)
"Effective Early Reading" is a comprehensive guide aimed at educators and parents focused on fostering reading skills in young children. The book emphasizes evidence-based strategies for teaching phonics, comprehension, and fluency, providing practical tips and activities to engage young learners.